2022
DOI: 10.3390/jcm11154553
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits Most? Interactions between Personality Traits and Outcomes of Four Incremental Meditation and Yoga Treatments

Abstract: Mind–Body Medicine (MBM) includes a broad range of interventions with proven preventive and clinical value, such as yoga and meditation. However, people differ in their preferences and response to different MBM treatments and it remains unclear who benefits most from what type of practice. Thus, finding moderators of treatment outcome seems to be a promising approach. This was the aim of the present study. We conducted a single-case multiple-baseline study investigating the outcomes and moderators of four diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Specifically, participants might be more aware or more mindful toward their inner experience during the treatment and, thus, adjust their responses [ 89 , 90 ]. Similarly, individual characteristics might influence a participant’s response to the different yoga components [ 9 , 48 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, participants might be more aware or more mindful toward their inner experience during the treatment and, thus, adjust their responses [ 89 , 90 ]. Similarly, individual characteristics might influence a participant’s response to the different yoga components [ 9 , 48 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is a secondary analysis of data that was previously reported by Matko et al [ 47 , 48 ]. It expands the previously reported findings by providing a detailed analysis of affectivity, body awareness, emotion regulation, distress tolerance, and self-compassion.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is considered a concise and sufficiently reliable and valid instrument. Trait absorption describes a person's disposition to become fully engaged ("absorbed") in experiences and was related to meditation outcomes (Hölzel & Ott, 2006;Matko et al, 2022a). We measured it using the 34-item modified German version of the Tellegen Absorption Scale (Ritz & Dahme, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…It is considered an economic and sufficiently reliable and valid instrument. Trait absorption describes a person's disposition to become fully engaged ("absorbed") in experiences and was often related to favorable meditation outcomes (Hölzel & Ott, 2006;Matko, Berghöfer, et al, 2022). We measured it using the 34-item modified German version of the Tellegen Absorption Scale (Ritz & Dahme, 1995).…”
Section: Methodsmentioning
confidence: 99%